Family psychoeducation to improve outcome in caregivers and patients with schizophrenia: a randomized clinical trial - Tessier, Arnaud; Roger, Karine; Gregoire, Alexandra; Desnavailles, Pauline; Misdrahi, David (Frontiers in Psychiatry, 2023)
Introduction Schizophrenia is recognized for its severe impact on both patients and caregivers. In a 12-month follow-up randomized clinical trial, we aimed to measure the efficacy of a brief family psychoeducation program in terms of reducing relapse risk and improving medication adherence in patients, as well as reducing caregiver burden, depression and increasing knowledge of the illness. Methods A total of 25 days of patients with schizophrenia (DSM-IV-TR) and family primary caregivers were recruited in a single regional psychiatric outpatient facility located in Bordeaux. In the active group, caregivers received a psychoeducational intervention consisting of six sessions spread over 1.5 months, while the control group was placed on a waiting list. Sociodemographic, symptom severity (PANSS) and medication adherence (MARS) from patients were assessed at baseline and relapse rates was recorded during the 12 months follow-up period. Caregivers’ burden (ZBI), depression (CES-D), quality of life (S-CGQoL), knowledge of the disease (KAST) and therapeutic alliance (4PAS-C) were assessed at baseline, three and 6 months. Results On the 25 patients included, the mean age was 33.3 years (SD = 9.7) with a mean duration of disease of 7.48 years (SD = 7.1). On the 25 caregivers included, the mean age was 50.6 years (SD = 14.0). Twenty-one were female (84.0%), 12 were married (48.0%) and 11 lived alone (44.0%). For patients, the family psychoeducation intervention significantly reduced the risk of relapse with a significant effect found at 12 months follow-up (p = 0.014). No change was observed on medication adherence. For caregivers, the intervention reduced the burden (p = 0.031), decreased the depression (p = 0.019), and increased the knowledge on schizophrenia (p = 0.024). Analyzes for repeated measures showed a statistically significant difference in therapeutic alliance (p = 0.035). Conclusion As confirmed by previous studies, the brief multifamily program (consisting of six sessions over a period of 1.5 months) was found to be effective in improving outcomes for caregivers (e.g., burden, depression, knowledge) and patients (e.g., preventing relapse) in the context of routine care. Given its short duration, this program is expected to be easily implementable within the community. Clinical trial registration https://clinicaltrials.gov/, NCT03000985.